The effects of pulsed static and oscillating magnetic fields on rat pineal serotonin N-acetyltransferase activity - Isaacs, Ian J (Division of Physiological Sciences, 2018)
Concerns about the possible hazardous effects of electromagnetic fields (EMF ' s) has resulted in attempts to address this issue. Several authors have shown that EMF exposure affects biological systems and more specifically the pineal enzyme, serotonin N-acetyltransferase (SNAT), inhibiting the enzyme and thus melatonin production. The enzyme assay required, for performing this type of work is crucial, as the natural decay of the enzyme could bias experimental results. An assay for measuring SNAT activity was assessed and then improved. The Ca²⁺ ion chelator, EGTA (2mM), preserved enzyme activity during pineal homogenisation. The enzyme is heat sensitive and thus keeping the homogenates on ice facilitated enzyme preservation. Not only was preservation of the enzyme crucial, but optimum substrate concentrations were required to measure maximum levels of SNAT activity. Maximum levels of activity were measured when I/10th of a pineal gland was incubated with 12mM tryptamine. At the specified tryptamine concentration, SNAT activity increased as the concentration of Acetyl CoA increased. The enzyme efficiency, as determined from its Km (8.19x10⁻⁴M), and the level of activity exceeded those measured in other laboratories. This assay was used to determine SNAT activity following magnetic field exposure. The magnetic field studies investigated the effects of pulsed static and oscillating magnetic fields on SNAT activity. Male Long Evans rats were housed in short and long photoperiods and were exposed for either 60mins., 30mins. or 15mins. to magnetic fields at different times during the dark phase. Rats were exposed to regularly repeated inversion of either the vertical or horizontal component of the earth' s magnetic field or to regularly repeated horizontal or vertical lOOμT DC field inversions. Pulsed static magnetic field exposure in all conditions had no significant inhibitory effect on SNAT activity. Oscillating magnetic field studies investigated the effect of exposure of rats to magnetic fields tuned to ion parametric resonance conditions for Ca²⁺. The ion parametric resonance model of Blanchard and Blackman was used to determine the exposure parameters. Rats were thus exposed for an hour to a vertical AC field, of strength 14.3μT (rms), frequency was 17.2Hz while the strength of the vertical DC field was 22.55μT, the existing vertical geomagnetic field strength. Under these conditions oscillating magnetic field exposure also had no significant inhibitory effect on SNAT activity.